A systematic review of the benefits of and barriers to development of outreach training for undergraduate dental students - Burns, Angus (Trinity College (Dublin, Ireland). School of Education, 2022)
ABSTRACT Angus Burns A systematic review of the benefits of and barriers to development of outreach training for undergraduate dental students Dental “outreach training” is clinical training for undergraduate dental students, which takes place in a setting away from their university dental school or dental hospital, with a view to exposing students to more experiential learning. A systematic literature review was undertaken to examine the extent to which outreach training enhances dental science curricula. The supports required along with the barriers and challenges to the introduction of dental outreach training were also reviewed. Both quantitative and qualitative studies were considered and a quality control tool was applied to establish a minimum standard for inclusion of research in the review. Evidence from quantitative research was grouped and thematic analysis was used to generate themes and sub-themes from the included qualitative studies. Following application of the inclusion and exclusion criteria and utilisation of the quality control tool 17 studies were ultimately included in the review. Positive findings from the included quantitative research were that students who had completed outreach training either performed similarly in summative assessments to students who had not completed outreach training or outperforming their traditionally-trained peers. Students completed more treatment in outreach settings compared to exclusively dental hospital-based training and had higher levels of self-perceived clinical confidence. Outreach-trained students also perceived that they developed additional skills, increased their productivity and self-confidence and gained more “real world” experiences as a result of their external placements. Adequate facilities and access to basic equipment were highlighted as important issues to support outreach training in addition to co-operation between the dental school and the outreach setting. Training and ongoing support for clinical staff within the outreach settings were recognised as key elements for successful placements. Challenges which emerged for students undertaking outreach training included, perceived lack of variety of treatment types and inconsistency in clinical opportunities between different outreach settings. From the perspective of the outreach settings themselves, identified barriers to training students included the disruption to clinics and the regular dental service as a result of hosting students to facilitate their trainings along with some concerns about patient safety. The precise purpose of individual outreach placements needs to be defined and outreach staff require training and ongoing support from the dental schools. Students need to be clearly appraised regarding the purpose of an outreach placement and afforded opportunities to adequately prepare for the experience.
Keywords: Higher Education; Education